Acute Respiratory Distress Syndrome (ARDS) Management Severe COVID-19 - Irianto, Helen Yudi; Jufan, Akhmad Yun (Faculty of Medicine-Universitas Airlangga, 2023)
Introduction: The Coronavirus disease 2019 (COVID-19) caused a global pandemic and many management challenges. Acute Respiratory Distress Syndrome (ARDS) is one of the most common pneumonia complications in COVID-19 cases. ARDS in COVID-19 have worse outcomes and increased risk of intensive care unit (ICU) admission. Objective: This case report aims to recognize and understand ARDS management in a severe COVID-19 case. Case Report: A 68-year-old man with diabetes mellitus and hypertension arrived at the Emergency Room (ER) after experiencing five days of fever, cough, diarrhea with frequency of four times a day, weakness, and a positive antigen result for COVID-19 at admission. Anosmia was absent. The patient had been vaccinated for COVID-19 twice. The main problem was his desaturation of 88%, blood pressure of 156/73 mmHg, heart rate of 80x/minute, and respiratory rate of 20x/minute. However, the patient was alert and admitted to the isolation ward. After 21 days of hospitalization, the patient's condition worsened. The patient developed ARDS and was referred to the COVID ICU for 25 days and 20 days to the non-COVID ICU, where he was intubated, and a tracheostomy was performed. After 45 days of admission to the ICU, the patient's condition improved. Discussion: COVID-19 patients with ARDS should be immediately intubated when conditions such as dyspnea, RR>30x/min, SpO2<92% (for patients with no comorbidities) or <95% (for patients with comorbidities), unconsciousness, or shock appears. Furthermore, other conditions, such as an HR> of 120x/min and a ROX index of <3.851, should be considered an indication for intubation. Conclusion: Timely intubation improves the outcome of COVID-19 patients with ARDS.